2004
DOI: 10.14411/eje.2004.065
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness in Ostrinia nubilalis (Lepidoptera: Pyralidae): Glycerol content, hexose monophosphate shunt activity, and antioxidative defense system

Abstract: Abstract. Many insects in temperate regions overwinter in diapause, during which they are cold hardy. In these insects, one of the metabolic adaptations to the unfavorable environmental conditions is the synthesis of cryoprotectants/anhydroprotectants. The aim of this study was to investigate the connection between the antioxidative system and synthesis of cryoprotectants (mainly glycerol) in diapausing larvae of the European corn borer, Ostrinia nubilalis (Lepidoptera: Pyralidae). At two periods during diapau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 51 publications
1
29
0
1
Order By: Relevance
“…In larvae, antioxidant levels are crucial Antioxidant system of Osmia bees for subsequent developmental stages (JovanovicGalovic et al 2004). It has been suggested that antioxidant enzymes have overlapping functions to promote stable development and homeostasis during diapause and metamorphosis (Stanic et al 2004). The above observations explain the activity of antioxidant enzymes and non-enzymatic antioxidants in all examined stages of O. bicornis ontogenesis (Figs.…”
Section: Discussionmentioning
confidence: 60%
“…In larvae, antioxidant levels are crucial Antioxidant system of Osmia bees for subsequent developmental stages (JovanovicGalovic et al 2004). It has been suggested that antioxidant enzymes have overlapping functions to promote stable development and homeostasis during diapause and metamorphosis (Stanic et al 2004). The above observations explain the activity of antioxidant enzymes and non-enzymatic antioxidants in all examined stages of O. bicornis ontogenesis (Figs.…”
Section: Discussionmentioning
confidence: 60%
“…No statistically significant changes in total antioxidant status, GSH, superoxide dismutase or nonspecific peroxidase values are noted in overwintering males or females. The absence of changes in superoxide dismutase level is unexpected because this enzyme protects other insects against oxidative stress induced by low temperatures (Grubor‐Lajsic et al ., ; Stanic et al ., ; Sim & Denlinger, ). Other studies demonstrate that superoxide dismutase, catalase and peroxidase have protective functions in diapausing Culex pipens and Grapholita molesta (Sim & Denlinger, ; He et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the different species could be attributed to variations in diapause behaviour of the analyzed insects (Koštál, ). The discrepant results reported by various studies could also indicate the specificity of antioxidant systems in different insects (Joanisse & Storey, ; Stanic et al ., ; He et al ., ). In diapausing C. pipiens , catalase protects the resting ovaries against oxidative damage (Sim & Denlinger, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies (Stanic et al, 2004) show that the biosynthesis of glycerol as a cryoprotectant is closely associated with antioxidant enzymes in larvae of the European corn borer, Ostrinia nubilalis. The elevated activity of enzymes in the pentose phosphate pathway in Ostrinia larvae exposed to cold accord with data on the glycerol synthesis pathway (Nordin et al, 1984).…”
Section: Introductionmentioning
confidence: 93%